Keterbukaan Informasi Publik Bentuk Keseriusan Pemerintah Menuju Good Governance (Implementasi Undang Undang Nomor 14 Tahun 2008) - Ade Suhendar (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2010)
Publik information has become a right of every person, having in his pass legislation to make Publik disclosure of Publik information or other institution has the legal power to obtain information about the implementation of governance. This as evidence of the government's seriousness in undertaking reforms in order to provide the best service to the community, people directly involved in the execution of state administration as a control. As a provider of information, each Publik agency shall provide all information relating to the implementation of activities and budget to all parties so that its implementation will continue to minimize the things that are not desirable, such as corruption, collusion and nepotism.